Effect of Upper Eyelid Blepharoplasty on Vision and Corneal Tomographic Changes Measured By Pentacam. (3rd September 2015) - Simsek, Ilke Bahceci; Yilmaz, Basak; Yildiz, Serra; Artunay, Ozgur
Abstract: Purpose : The aim of this study is to determine whether any change occurs in corneal astigmatic values measured by a pentacam and any subjective visual acuity changes occurs following the upper eyelid blepharoplasty. Methods : This is a prospective study; 43 eyes of 23 patients with dermatochalasis underwent pentacam and surveyed for blurred vision before, 1 and 3 months after blepharoplasty surgery. In the course of those 3 measurements, both refractive and keratometric data were recorded and analyzed. The changes in refractive sphere, cylinder and cylindrical axis from both preoperative and postoperative readings were compared statistically. Results : Compared to preoperative measurements, 26 eyes (60%) had a measurable increase in corneal astigmatism after the surgery. Increased astigmatism observed by pentacam in the first and the third month after surgery, showed statistically significant results according to Wilcoxon test with ( p = 0.028 < 0.05) and ( p = 0.048 < 0.05) values, respectively. The mean change in astigmatism was reported as 0.15D. Regarding the astigmatism axis, no significant change was detected; in the 1 month ( p = 0.435 > 0.05) and 3 months ( p = 0.560 > 0.05) postoperative measurements compared to preoperative values. Two patients (4.34%) reported visual acuity change 3 months after the surgery. Conclusıon : We discovered statistically significant astigmatic changes; however, these were clinically insignificant visual acuity changes in compatibility with prior studies. Patients undergoing blepharoplasty surgery should be advised that this procedure may potentially alter vision. It is also very important to advise the patients to undergo cataract and/or refractive surgery after having upper eyelid surgery that this procedure may induce vision changes.